Assessing Financial System Vulnerabilities - Johnston, R. (IMF Working Papers; Working Paper, 2000)
Recent financial crises have highlighted the potentially significant macroeconomic costs of financial system instability, and the potential for the instability in the financial system of one country to have broader implications for the stability of financial systems and macroeconomic performance in other countries. This paper reviews the different analytical approaches to assessing vulnerabilities in the financial systems and the benefits and limitations of the different approaches, and suggests enhancements that could help strengthen financial system stability assessments.